Обгрунтування конструкції чотирилопатевого відцентрового розкидача мінеральних добрив - Кобець, А. С.; Науменко, М. М.; Пономаренко, Н. О.; Kobets, Anatoliy; Naumenko, N.; Ponomarenko, Nataha (КНТУ, 2013)
Запропоновано роторний робочий орган, конструкційні особливості якого дозволяють покращити рівномірність розсіювання мінеральних добрив. Investigational construction features of rotor working organ and their influence on the high-quality indexes of work of throwing about of mineral fertilizers. The obtained formulae allow to determine the absolute velocity fat disk and angle of departure required for determining the width of the lens cover. On the basis of analysis of motion of financial particle for the blades of centrifugal working organ along a sending rib structural descriptions of the fourblade throwing about are grounded. Withdrawn simple enough for engineering application of the formula, giving an opportunity to substantiate the design of the disk diffuser fertilizers, which is guaranteed to improve scattering.
Rationale for the construction of centrifugal spreader of mineral fertilizers
Keywords: мінеральні добрива; розкидач відцентрового типу; лопаті; відцентровий робочий орган; диск; рівномірне розміщення гранул; mineral fertilizer spreader centrifugal type blades; centrifugal working body; disc; even distribution of granules